National-Cultural Features of Causal Semantics Representation by Phraseological Means of Russian Language - O. V. Kolesnikova (Научный диалог, 2018)
The article is devoted to description of a number of phraseological units with the causal semantics. Units of the following semantic groups are analyzed: “To Make. To Force,” “To Subdue,” “To Harass. To Exploit.” Causation is understood widely with inclusion in this concept of causal, concessive and target relations. The specified semantics is verbalized through idioms that describe a particular causal situation. This situation implies the presence of causator (active participant), causable person or object (passive participants). Central component of the studied phraseological units is a causative verb in the infinitive form. Linguistic and cultural analysis allows the author to reveal national and cultural peculiarities of the representation of the causal semantics on the level of phraseology. It is shown that influence of causator on face being caused in the Russian mentality is negatively assessed in most cases and correlates with physical impact on him, limiting his actions. The main images of phraseology of specified semantics are described. In a phraseological unit such components as head , mind , intelligence , soul ( heart ), symbolizing the organs that are affected, are frequent. The structure of the semantic groups with semantic isolation of the series is presented. Synonymic and antonymic relations within these associations are described. Polysemy links at phraseology level are characterized.